Mesozoic Collision-Related Structures in the Southern Tarim Basin, W. China: Implications for the Paleo-Tethys Closing Process - Li, Yong; Wen, Lei; Yang, Xian-Zhang; Li, Cheng; Zhang, Liang; Wang, Bin; Chen, Cai; Liu, Ya-Lei; Li, Yue-Jun (Frontiers in Earth Science, 2022)
The Mesozoic syn- and post-collision structures were revealed in the southern Tarim Basin based on careful seismic interpretation and field investigation. The syn-collision structures are the Late Triassic thrusts in the piedmonts of W. Kunlun and Altun Mountains and the Markit Slope. They include both newly formed thrusts and reactivation of some preexisting thrusts, such as the Qarqan fault in the piedmont of the Altun Mountains. The post-collision structures are the Jurassic–Cretaceous normal faults, with the development of horsts and grabens. In the Late Triassic, the maximum stress was SSW-NNE-directed in the piedmont of the W. Kunlun Mountains and the Markit Slope but SSE-NNW-directed in the piedmont of the Altun Mountains, forming many reverse faults thrusting from the mountains to the Tarim Basin with the development of some back-thrusts in the Markit Slope. They are the syn-collision structures in response to the North Qiangtang–Tarim collision. This Late Triassic collision is an important tectonic event in the complicated closing process of the Paleo-Tethys. The Jurassic–Cretaceous extensional structures are the post-collision structures.